Analysis Of The Use Of The Sakti Application System In Managing Financial Reports At The National Narcotics Agency Of Karawang Regency - Dian Mardiana; Sihabudin; Robby Fauji (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — This study aims to understand the implementation of the SAKTI application in financial management at the Karawang Narcotics Agency (BNN Karawang), particularly in improving the efficiency and effectiveness of financial reporting and administrative processes Research method—The research uses a qualitative descriptive approach. Data were collected through observation, interviews, literature study, and triangulation to ensure accuracy and credibility of the findings Result— The implementation of the SAKTI application at BNN Karawang began in early 2022. Although relatively new, the application has been effectively and optimally utilized. It simplifies financial administration tasks, allows multiple financial operations within a single platform, minimizes system errors or crashes during data processing, and successfully replaces the previous financial recording system. However, employees still require additional training and deeper understanding to maximize the application’s potential. Conclusion— The SAKTI application supports and enhances financial management at BNN Karawang without altering the fundamental roles and functions of financial recording. It streamlines operations and improves data accuracy, indicating a positive shift toward digitalized and integrated financial systems in government agencie.